The Effect of Problem Posing Learning Model and Student Attitudes on Mathematics Learning on the Critical Thinking Ability of Mathematics Students in Grade VIII of SMPN 6 Percut Sei Tuan - Giawa, Freddy; Simanjorang, Mangaratua Marianus; Khairani, Nerly (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study examines the influence of the Problem Posing learning model and students' attitudes towards mathematics on the critical thinking skills of grade VIII students of SMPN 6 Percut Sei Tuan. Using a quasi-experimental approach with two groups, the experimental group taught using the Problem Posing model and the control group taught using regular learning, this study aims to analyze the effectiveness of Problem Posing in developing critical thinking skills. Data was collected through critical thinking skills tests (pretest and posttest) and mathematical attitude questionnaires during the odd semester of the 2024/2025 school year. The results of the two-track ANOVA analysis with a significance level of 0.05 showed that the Problem Posing learning model had a significant influence on students' critical thinking skills (F=28.789; sig.=0.000<0.05). Furthermore, students' attitudes towards mathematics which were categorized as high, medium, and low were also proven to have a significant effect on critical thinking skills (F=6.769; sig.=0.000<0.05). However, this study did not find any interaction between the Problem Posing learning model and students' attitudes in influencing critical thinking skills (F=0.658; sig.=0.532>0.05), which indicates that these two variables contribute to influence independently without moderation effects. These findings suggest that the Problem Posing model can effectively improve students' critical thinking skills regardless of their attitude towards mathematics, while a positive attitude towards mathematics in general contributes to better critical thinking skills.